HERMENEUTIC PRINCIPLES OF GENERAL JUSTICE IN CIVIL CASES - Fajar Rachmad Dwi Miarsa; M. Zamroni (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
In the dispute of civil cases filed to the judiciary, the justice seekers seeking justice through the court hope to be able to do it quickly and lawfully. However, in reality the process through the judiciary is not as hopeful, as the principle of justice should be done simply, quickly and costly. The purpose of this paper is to understand the application of the principle of justice done with a simple, quick and light cost with the method of approach used in this study is the normative-empirical law research is a combination of normative legal research with empirical law research. The principle of the judiciary set forth in Article 2 paragraph (4) of Act Number 48 of 2009 on Judicial Power, should be done simply, quickly and lightly and efficiently and effectively and not ruling out precision and accuracy in seeking truth and justice. The application of the principle of justice depends to a great extent on the legal officers of such bodies, especially in the courts and the supreme court of the administrative authorities as well as of the judges handling cases.